INEQUALITY AND WELFARE STATE CLIENTELISM IN BOSNIA AND HERZEGOVINA - Obradović, Nikolina; Patrick Filic, Goran (Economic Annals, 2019)
Inequality in Bosnia and Herzegovina (BiH) is rampant, manifested not only through one of the highest Gini coefficients in Europe but also in unequal access to social benefits and services. We find this to be an outcome of BiH’s entity-government social policy, which has been created to serve ethnic clientelistic politics. As the country’s former social protection system adjusted in the immediate post-civil war period to a new asymmetric govern-ment structure made of two entities, Fed-eration of Bosnia and Herzegovina and Re-publika Srpska, it helped the main ethnic political parties preserve their power and ethnic divisions. This was achieved through a comprehensive system of status-based so-cial benefits, most notably war-related so-cial benefits granted on the basis of ethnic and military service affiliation. As such, in both BiH’s entities the system of social protection is an instrument of political con-trol that generates inequality by treating certain social groups differently in terms of access to and level of benefits, while exclud-ing much of the population. The process is found to be endogenous; in other words, maintaining inequality in access to social benefits is essential for preserving clientelis-tic policy, and vice versa.